3D-printed ceramic triply periodic minimal surface structures for design of functionally graded bone implants. (June 2020) - Vijayavenkataraman, Sanjairaj; Kuan, Lai Yee; Lu, Wen Feng
Abstract: Stress shielding is one of the main problems that lead to bone resorption and revision surgery after implantation. Most of the commercially available metallic non-porous bone implants have a much greater stiffness than the native human bones and are prone to cause stress-shielding. With an open cell structure and intricate architecture, hyperbolic minimal surfaces offer several advantages such as less stress concentration, high permeability and high surface area to volume ratio, thus providing an ideal environment for cell adhesion, migration, and proliferation. This paper explores the use of porous bone implant design based on Triply Periodic Minimal Surfaces (TPMS) which is additively manufactured with ceramic material (Alumina) using Lithography-based Ceramics Manufacturing (LCM) technology. A total of 12 different primitive surface structure unit cells with pore size in the range of 500–1000 μm and porosity above 50% were considered. This is one of the earliest studies reporting the 3D printing of TPMS-based structures using ceramic material. Our results suggest that the choice of material and a porous TPMS-based design led to fabrication of structures with a much lesser compressive modulus comparable with the native bone and hence could potentially be adopted for bone implant design to mitigate the stress-shielding effect. Graphical abstract: Unlabelled Image Highlights: 3D-printed ceramic hyperbolic surface structures exhibit Young's modulus values between 2-5.5 GPa comparable to native bone The open cell structure & intricate architecture offer conducive cell-microenvironment (high surface area to volume ratio) Difficulty in slurry removal with smaller unit cell sizes (<2 mm) resulted in greater mass deviations (up to 100%) An equation is derived to find the theoretical Young's modulus of the printed structures for proprietary materials A functionally-graded structure for the trochanter region of hip implant is designed to mitigate stress-shielding effects